2002
DOI: 10.1001/jama.287.16.2106
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Blacks and Whites After a Cancer Diagnosis

Abstract: Only modest cancer-specific survival differences are evident for blacks and whites treated comparably for similar-stage cancer. Therefore, differences in cancer biology between racial groups are unlikely to be responsible for a substantial portion of the survival discrepancy. Differences in treatment, stage at presentation, and mortality from other diseases should represent the primary targets of research and interventions designed to reduce disparities in cancer outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
298
3
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 457 publications
(316 citation statements)
references
References 84 publications
11
298
3
2
Order By: Relevance
“…In striking contrast to studies that demonstrated an association between nonwhite race and inferior cancer care and, ultimately, unfavorable long-term survival, [14][15][16][17][18][19][20][21] we observed that nonwhite race predicted improved surgical care, as defined by adequate lymph node evaluation. Because African Americans and Hispanics tend to be uninsured and of lower socioeconomic status, it is possible that university centers are the likely providers of their surgical care: These findings are contrary to popular opinion.…”
Section: Discussioncontrasting
confidence: 99%
“…In striking contrast to studies that demonstrated an association between nonwhite race and inferior cancer care and, ultimately, unfavorable long-term survival, [14][15][16][17][18][19][20][21] we observed that nonwhite race predicted improved surgical care, as defined by adequate lymph node evaluation. Because African Americans and Hispanics tend to be uninsured and of lower socioeconomic status, it is possible that university centers are the likely providers of their surgical care: These findings are contrary to popular opinion.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies show that access to quality care and socioeconomic factors that limit access can have a significant role in cancer survival in men of different racial/ethnic backgrounds. 18,19 Potentially the lack of access to early detection programs and cancer screening explains part of the disparity in prostate cancer presentation. However, other investigators reported racial and ethnic disparities that persist after controlling for socioeconomic factors and access to medical care, and found that most cancer in this population is still detected by screening.…”
Section: Resultsmentioning
confidence: 99%
“…18,26 Blacks are more likely than whites to have aggressive histologic variants that result in a worse prognosis even with adjustment for grade, stage, and treatment. 18,23,26,27 Blacks are less likely to undergo definitive surgery, more likely to be treated by low-volume providers and in low-volume hospital settings, and more likely to experience adverse treatment-related outcomes. [28][29][30][31][32] While our data showed that black patients who accessed care were as equally likely as whites to undergo complete hematuria evaluations, our ability to identify differences in health system engagement between races is limited by the obvious selection bias inherent to claims data of insured individuals.…”
Section: Discussionmentioning
confidence: 99%